PENERAPAN SISTEM IRIGASI TETES BERBAGAI VOLUME AIR DAN MEDIA TANAM TERHADAP PRODUKSI BAWANG MERAH (Allium ascalunicum L.) - Triana, Arjuna Neni; Hersyamsi, Hersyamsi; Yanto, Sri (Politeknik Negeri Lampung., 2025)
This study aims to determine the effect of various organic growing media with different water volume percentages on the growth of red onion plants (Allium ascalunicum L.) using drip irrigation. The research method used was a Factorial Randomized Block Design (RBD) with treatment factors of water volume percentage (A) and growing media combination (B) with three replications. The observed parameters were soil moisture content, water supply efficiency, and plant growth including plant height, number of leaves, bulb weight, and bulb diameter. The results showed the highest water content at A1B2, which was 65.04%, and the lowest water content at A3B3, which was 38.39%. The best water use efficiency was A1B3, which was 3.21 kg/m³, while the lowest efficiency was A3B2, which was 0.12 kg/m³. The tallest plant was A1B3, which was 47.30 cm, and the shortest was A2B2, which was 16.66 cm. Water supply and various growing media treatments affected the number of leaves, with the most at A1B3, which was 7.23 leaves, and the least at A2B2, which was 3.70 leaves. The largest bulb diameter was A1B1, which was 3.33 cm, and the smallest was A2B4, which was 0.92 cm. The results of the advanced test BNJ 5% showed that the bulb diameter of treatments A3, A2, and A1 had a significant effect on each other. The largest bulb weight was at treatment A1, which was 4.60 grams, and the smallest was A3, which was 2.79 grams. Bulb weight measurement at treatment A1B3 had an average weight of 3.58 grams, while the lowest was at A2B4 with 0.57 grams. The combination of water supply and various growing media had a significant effect on soil moisture content, water efficiency, and plant growth.